Mechanics of machines - Cleghorn, William L.; Dechev, Nikolai (Oxford University Press, 2015)
Mechanics of Machines, Second edition, is ideal for courses in kinematics and dynamics of machines. It covers the basic concepts of gears, gear trains, the mechanics of rigid bodies, and graphical and analytical kinematic analyses of planar mechanisms. In addition, the text describes a procedure for designing disc-cam mechanisms, discusses graphical and analytical force analyses and balancing of planar mechanisms, illustrates common methods for synthesis of mechanisms, and covers design methodology for mechanisms. The companion website for students includes over 170 models and animations. This includes 2D and 3D mechanisms and machines, and video clips of real mechanical systems in operation. It also features scaled drawings and Mathcad files for use with end-of-chapter problems.